(3eNJUQ aj SjQI GdfHi Udi Gddg Ydjg hSdes - (3CHh eMeO YHO GdeDef Hf Nda GdOejGWj, TQa GdOjf,J (B705 (3g` s ((3eMeO Hf eMeO GdEeGe s)
(3ChdgG (B:s
(3GdMeO ddg fMeOg hfSJYjfg CeG HYO aEf CMSf GdMOjK cJGH Gddg gPg GdNWHI eCKhQI Yf GdfHi Udi Gddg Ydjg hSde , LeYJ ef CMGOjK TJi , hEfi bO ESJNQJ Gddg JYGdi ai LeY cJGH eNJUQ ai SjQI s
(3BNQgG (B:s
(3hYf CfS Hf eGdc bGd (B: (3deG cGf Gdjhe GdPi bHV ajg QShd Gddg Udi Gddg Ydjg hSde CXde efgG (B_ (3jYfi GdeOjfI (B_ (3cd TF , heG faVfG Yfg GdCjOi ef Oafg MJi CfcfG bdhHfG hgPG BNQ GdcJGH hddg GdMeO s
(3HgG fXGe GdJYbjHIs
(3cJHJ GdYfGhjje hGdCSGfjO HGdMeQIs
(3YdjgG JbjjOGJ cKjQI s
(3YdjgG JedcGJ ai GdbQf GdKGdK YTQ s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
Keywords: (3GdJGQjNs